Analisa Penggunaan Support Frame Lama Pada Desain Baru Screw Conveyor Machine Menggunakan Metode Elemen Hingga - Kristiawan, Timotius Anggit; Alisyafa’at, Ahmad Dhimas; Yanuar, Padang; Setiyawan, Trio (Universitas Nusantara PGRI Kediri, 2023)
Frame construction is one of the things that must be considered in the process of designing a machine, for that the design of the strength of the frame is an important thing in order to withstand the load and support the various components contained in the machine and analyze the strength of the frame related to the capacity of the screw conveyor machine.This study aims to analyze the structural strength of the Support frame which is used to support the new design of the screw conveyor machine in the process of moving and draining wet plastic pieces. The method used in this design includes collecting data, creating a 3D model using solidwork software, then analyzing the structure using the Finite Element Analysis (FEA) simulation method. The results of the FEA simulation on the truss construction with a loading of 4,049 N get the highest stress value (stress) with the centralized loading method of while with the uniform loading method of , compared to the yield strength value of 250.000.000 the support fream construction is safe to use, the displacement (deflection) with the uniform loading method is 0.4 mm while the concentrated loading method is 0.77mm, The simulation results of factor of safety analysis from uniform loading are 10 while for the centralized loading method the factor of safety value is 4, so it is concluded that this design is feasible to use and the safety factor is good.